There's a boy in the girls bathroom - Sachar, Louis (New York : Alfred A. Knopf, 1987)
An unmanageable, but lovable, eleven-year-old misfit learns to believe in himself when he gets to know the new school counselor, who is a sort of misfit too.
Keywords: Behavior; Friendship; Schools; Counselors